Applying the carbon materials in TSVs array for enhancing heat transfer performance of three-dimensional integrated circuits - Peng Xu; Huan Huang; Songjie Zhao; Xiushan Liu; Fa Zou; Chao Li; Jun Ai; Hui Liu (Case Studies in Thermal Engineering)
This paper proposed the carbon materials (including MLGNR, MWCNT and SWCNT) to replace the traditional Cu as the filler of through silicon via (TSV) for enhancing heat transfer performance of three-dimensional integrated circuits (3-D ICs), meanwhile the corresponding mathematical model is established to quickly obtain steady-state temperature of each die layer. The results indicated that the steady-state temperature of 3-D ICs with inserted MLGNR, MWCNT and SWCNT based TSVs array are reduced by 23.315 %, 29.043 % and 38.007 % respectively, as compared with Cu as the filler of TSV. Moreover, it is manifested that the heat transfer performance of 3-D ICs can be further improved by increasing the number and radius of TSV. The corresponding steady-state temperature of the scheme of 5 × 6 TSVs array is 10.415 % lower than that of the scheme of 4 × 4 TSVs array, in the meantime the steady-state temperature can be reduced by 16.016 % when the radius of TSV increases from 1.5 μm to 2.5 μm. Furthermore, it is demonstrated that the processor runtime and memory footprint of our proposed model are 46.938 and 6.771 times lower than COMSOL simulation model, and the maximum error between them is not exceeding 3 %.